2016
DOI: 10.1111/roie.12212
|View full text |Cite
|
Sign up to set email alerts
|

Pane e Cioccolata: The Impact of Native Attitudes on Return Migration

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The idea is that if migrants think that discrimination in France is widespread, they are certainly more likely to be willing to leave or return to their home country. de Coulon et al (2016) confirmed this in a recent quasi-experimental setting (i.e. the media coverage of a particularly tragic murder committed by a Romanian immigrant in Italy).…”
Section: Remigration Intentions and Home Outcomesmentioning
confidence: 55%
“…The idea is that if migrants think that discrimination in France is widespread, they are certainly more likely to be willing to leave or return to their home country. de Coulon et al (2016) confirmed this in a recent quasi-experimental setting (i.e. the media coverage of a particularly tragic murder committed by a Romanian immigrant in Italy).…”
Section: Remigration Intentions and Home Outcomesmentioning
confidence: 55%
“…10 As argued by Wilde (2000) and similarly by Greene (2008), identification is achieved through functional form in recursive bivariate models. 11 However, we still include exclusion restriction X i to provide plausibly exogenous variation in remigration intentions, R i . Our coefficient of interest is β 1 capturing the impact of remigration intentions on the outcome.…”
Section: Remigration Intentions and Home Outcomesmentioning
confidence: 99%
“…To the best of my knowledge, the only three studies that mention the possible effects of attitudes toward migrants on the skill level of migrants are Coulon et al (2016), Knabe et al (2013) and Slotwinski and Stutzer (2015). While these papers focus on single countries, I take a cross-country approach.…”
Section: Related Literaturementioning
confidence: 99%